Spontaneous switching and fine structure of donor–acceptor Stenhouse adducts on Au(111) - Senenko, Anton; Marchenko, Alexandr; Kurochkin, Oleksandr; Kapitanchuk, Oleksiy; Kravets, Mykola; Nazarenko, Vassili; Sashuk, Volodymyr (Nanoscale, 2025)
We present the spontaneous isomerization of donor–acceptor Stenhouse adducts anchored onto a gold surface, visualized using scanning tunneling spectroscopy. Our investigation reveals a palette of molecular arrangements, including those with ferroelectric-like ordering, evolving over time into a fine pattern consisting of both open and closed forms of the photoswitch.